Investigation on electrically conductive grounding materials produced by incorporating graphite and marconite - Nur Qurratul Ain Nadzirah, Mohd Nasir (2019)
The term earthing is defined as the connection of a conductor or frame of a device to the general mass of earth. The purpose is to disperse flow of charge to mother earth within the shortest time at the event of lightning and to ensure stable operation of power grid and electric accessory. This earth resistance depends on electrode arrangements as well as the surrounding soil resistivity. In this study, carbon-based material, namely graphite and Marconite were used as ground enhancement materials to improve the performance of earth grounding system. The study aims to determine the physical properties, establish carbon water retention curve (CWRC) at varying percentage of water content as well as to measure the electrical resistivity, water absorption and crushing strength of electrically conductive grounding materials. These materials were tested under powder and aggregated form. The CWRC was establish by using WP4C Potentia Meter and electrical resistivity were read using soil box method. At days 28, the aggregate with 1% by mass of graphite exhibited 49.2 Ω.m electrical resistivity, 12.61% water absorption and 7.45 N/mm² crushing strength. Comparing to Marconite, the aggregates with 1% Marconite possessed 39.2 Ω.m electrical resistivity, 12.93% water absorption and 11.11 N/mm² crushing strength. Results revealed that both material can be replaced as ground enhancement materials. However, Marconite is the best material to be use as an alternative grounding material due to having lower resistivity value, higher crushing strength and higher water absorption at days 28 compared to graphite.